Effect of polycarboxylate ether on the expansion of ye'elimite hydration in the presence of anhydrite. (February 2021) - Li, Chen; Li, Jiaqi; Telesca, Antonio; Marchon, Delphine; Xu, Ke; Marroccoli, Milena; Jiang, Zhengwu; Monteiro, Paulo J.M.
Abstract: Polycarboxylate ether (PCE), a commonly used superplasticizer, is known to influence the morphology of ettringite during the early hydration of C3 A- and ye'elimite-containing cements. According to existing theories, such morphological changes may be crucial to the expansive behavior of these cements. This paper studied the expansion of ye'elimite-anhydrite pastes and found the use of PCE to reduce expansion after 4 days of curing. Hydration studies were conducted by calorimetry, X-ray diffractometry, scanning electron microscopy, mercury intrusion porosimetry, inductively coupled plasma–optical emission spectrometry, and X-ray microtomography. The results show that the influences of PCE on the morphology of ettringite and the hydration of ye'elimite were quite small after 2 days. Based on the crystal growth theory, the range of pores in which ettringite can grow was calculated to explain the observed expansive behaviors. The presence of ettringite nano-crystals in aluminum hydroxide was also revealed and considered as a possible expansion mechanism.